Kebijakan Penerbitan Kartu Identitas Anak di Kota Semarang - Untung Sri Hardjanto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract The study aims to determine the policy of publishing identity cards for children in Semarang. The method of approach taken in this study is normative juridical. Data collection is obtained from the results of interviews and through library research. The data analysis method used is a qualitative descriptive analysis method. The results showed that the Regional Government of Semarang City in carrying out KIA issuance made PERDA No.4 of 2016, but its implementation was in 2017. Delay in the implementation of MCH due to the lack of coverage of ownership of birth certificates for children. The preparations made by the Semarang City Government in the context of the implementation of the MCH in 2017 are collecting data on children, discussing the additional benefits of KIA with several official agencies and the private sector, conducting comparative studies in regions that have implemented KIA and the basis of its arrangements. Preparation of the Regional Government of Semarang City in the issuance of KIA experienced several obstacles, among others, the unclear distribution of KIA forms, limitations and delays in budgeting, lack of competent human resources for the operation of SIAK. For ITU, the Semarang City Government made an effort to procure KIA sheets themselves, prepare computerized system training or SIAK, and make Mayor Regulations as technical implementation of Regional Regulation No.4 of 2016 concerning Implementation of Population Administration. Keywords: Child Identity Card, Policy, City of Semarang Abstrak Penelitian bertujuan untuk mengetahui kebijakan penerbitan kartu identitas anak di kota semarang . Metode pendekatan yang dilakukan dalam penelitian ini adalah yuridis normatif, Pengumpulan data diperoleh dari hasil wawancara dan melalui penelitian kepustakaan. Metode analisis data yang digunakan adalah metode analisa deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Pemerintah Daerah Kota Semarang dalam melaksanakan penerbitan KIA membuat PERDA No.4 Tahun 2016, namun pelaksanaannya pada tahun 2017. Keterlambatan pelaksanaan KIA karena masalah cakupan kepemilikan Akta Kelahiran anak yang masih kurang. Persiapan yang dilakukan Pemda Kota Semarang dalam rangka pelaksanaan KIA di tahun 2017 adalah mengumpulkan data anak-anak, membahas penambahan manfaat KIA dengan beberapa pihak dinas dan pihak swasta, melakukan studi banding ke daerah yang sudah melaksanakan KIA dan dasar pengaturannya. Persiapan Pemda Kota Semarang dalam penerbitan KIA mengalami beberapa kendala antara lain ketidakjelasan pendistribusian blanko KIA, keterbatasan dan keterlambatan pemberian anggaran, kurangnya sumber daya manusia yang kompeten untuk pengoperasian SIAK. Untuk ITU Pemda Kota Semarang melakukan upaya yakni pengadaan blanko KIA sendiri, mempersiapkan pelatihan sistem komputerisasi atau SIAK, dan membuat Peraturan Walikota sebagai pelaksanaan teknis dari Perda No.4 Tahun 2016 Tentang Penyelenggaraan Administrasi Kependudukan. Kata Kunci: Kartu Identitas Anak, Kebijakan, Kota Semarang